Application of Physiologically Based Pharmacokinetic Modeling to Evaluate the Drug–Drug and Drug–Disease Interactions of Apatinib - Liu, Hongrui; Yu, Yiqun; Guo, Nan; Wang, Xiaojuan; Han, Bing; Xiang, Xiaoqiang (Frontiers in Pharmacology, 2021)
Aim: Apatinib is an orally administered vascular epidermal growth factor receptor (VEGFR)-tyrosine kinase inhibitors (TKIs) approved for the treatment of advanced gastric adenocarcinoma or gastric esophageal junction adenocarcinoma. Apatinib is predominantly metabolized by CYP3A4, followed by CYP2D6. The present study aimed to evaluate the potential drug-drug interaction (DDI), as well as drug-disease interaction (DDZI) risks of apatinib in Chinese volunteers.Methods: Modeling and simulation was conducted using Simcyp Simulator. The input parameters required for modeling were obtained from literature research or experiments. Then, the developed physiologically-based pharmacokinetic (PBPK) models were applied to evaluate single-dose DDI potential in Chinese healthy volunteers with weak and moderate CYP3A inhibitors, strong CYP2D6 inhibitors, as well as CYP3A4 inducers. The DDZI potential was also predicted in patients with hepatic or renal impairment.Results: The developed PBPK models accurately assessed apatinib pharmacokinetics following single-dose administration in Chinese healthy volunteers and cancer patients. The DDI simulation showed 2 to 4-fold changes in apatinib exposures by moderate CYP3A4 inhibitors, and CYP3A4 inducers. A moderate increase of apatinib exposure (1.25 to 2-fold) was found with strong CYP2D6 inhibitor. In the DDZI simulation with hepatic impairment, the AUC of apatinib was significiently increased by 2.25-fold, 3.04-fold for Child-Pugh B and Child-Pugh C, respectively, with slightly decreased Cmax by 1.54, and 1.67-fold, respectively. Conclusion: The PBPK models developed in the present study would be highly beneficial to quantitatively predict the pharmacokinetic changes of apatinib under different circumstances which might be difficult to evaluate clinically, so as to avoid some risks in advance.